2014
DOI: 10.1016/j.envpol.2013.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of atmospheric particulate matter (PM) in rural field, rural village and urban areas of northern China

Abstract: a b s t r a c tAtmospheric PM 10 were measured for 12 months at 18 sites along a 2500 km profile across northern China. Annual mean PM 10 concentrations in urban, rural village, and rural field sites were 180 AE 171, 182 AE 154, and 128 AE 89 mg/m 3 , respectively. The similarities in PM 10 concentrations between urban and rural village sites suggest that strong localized emissions and severe contamination in rural residential areas are derived from solid fuels combustion in households. High PM 10 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…Such as, the total 18 PAHs concentration in fine particles in Nanjing was 50.6 ng m -3 during pre-Spring Festival (Kong et al, 2015); the concentration of PM 2.5 -associated 15 ∑PAHs was 22.54 ng m -3 during the autumn and winter in Nanchang (Liu et al, 2016); and 16 PAHs concentrations in PM 2.5 was 23.7 ng m -3 at Guangzhou with a heating source (Li et al, 2006). The lower PAHs concentration in South China compared with the present study sites may be attributed to the following reasons: no heating demand in winter, high precipitation frequency, and large precipitation intensity in South China (Li et al, 2014b). In addition, the PAHs concentrations in this study were higher than those in many areas of developed countries (Gigliotti et al, 2005;Motelay-Massei et al, 2005;Albinet et al, 2007;Romagnoli et al, 2014).…”
Section: Pahs Concentrations In Ambient Aircontrasting
confidence: 37%
“…Such as, the total 18 PAHs concentration in fine particles in Nanjing was 50.6 ng m -3 during pre-Spring Festival (Kong et al, 2015); the concentration of PM 2.5 -associated 15 ∑PAHs was 22.54 ng m -3 during the autumn and winter in Nanchang (Liu et al, 2016); and 16 PAHs concentrations in PM 2.5 was 23.7 ng m -3 at Guangzhou with a heating source (Li et al, 2006). The lower PAHs concentration in South China compared with the present study sites may be attributed to the following reasons: no heating demand in winter, high precipitation frequency, and large precipitation intensity in South China (Li et al, 2014b). In addition, the PAHs concentrations in this study were higher than those in many areas of developed countries (Gigliotti et al, 2005;Motelay-Massei et al, 2005;Albinet et al, 2007;Romagnoli et al, 2014).…”
Section: Pahs Concentrations In Ambient Aircontrasting
confidence: 37%
“…Field studies have observed comparable annual mean PM 10 (particulate matter with aerodynamic diameter equal or smaller than 10 micrometer) concentrations in urban areas (180 ± 171 μg·m −3 ) and rural villages (182 ± 154 μg·m −3 ) at 18 sites across northern China, suggesting that the severe outdoor air pollution in rural areas is partially derived from household solid fuel combustion (21). In 2013, the State Council issued the Action Plan, under which the BTH region is required to achieve a 25% reduction in annual mean PM 2.5 concentrations from the 2012 level by 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, most studies included for the meta-analysis were done in developed countries, and there was only one study from the developing countries. However, the data from developing countries may be more concerning because these regions are affected mostly by air pollution and may have the greatest potential to improve health by controlling air pollution and improving air quality (40). More studies from developing countries are needed to provide a more precise assessment of the influence of air pollution on diabetes-associated mortality.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%